Color atlas of ENT diagnosis - Bull, T. R.; Almeyda, John (Thieme, 2010)
Returning in a new edition, this popular color atlas is a concise visual guide for the diagnosis of the full range of ENT conditions. Incorporating the latest developments in the field, this edition opens with an overview of examination techniques, providing descriptions of instruments, imaging, and diagnostic tests. Separate sections cover common and uncommon disorders of the ear, nose, pharynx and larynx, and the head and neck. High-quality photographs are complemented by guidelines for the effective diagnosis and treatment of each clinical problem.